Traditional Homegardens in Rural Landscapes of Northeast India – A Model for Conserving Plant Species for Sustainability - Tangjang, Sumpam; Arunachalam, A. (Indian Journal of Hill Farming, 2018)
Call for natural resources management, biodiversity and environmental conservation related subjects are gaining momentum. Conservation scientists, researchers, Non-Governmental Organizations (NGOs) and policy makers are trying to address these issuesfrom local to global levels in all possible ways. In contrast to the present global scenario,the rural folks in the remote tribal inhabited northeast India are, however, silentlyconserving natural resources and are achieving sustainable agriculture with their richIndigenous Knowledge Systems (IKS). The study was carried out considering the role ofplant species in traditional homegardens for sustainability in Itanagar, Arunachal Pradeshand North Lakhimpur, Assam, two neighbouring Indian states located in the EasternHimalayas. We recorded 79 plant species belonging to 46 botanical families presenting amulti-tier canopy configuration with intimate mixture that provides a wide ranges ofservices such as folk medicine, construction material, timber, valuable food sources, cashincome,etc. Rice and arecanut were identified as important cultural as well as cash-cropsin North Lakhimpur while the farmers’ in Itanagar prefers more timber species. Theanalysis of existing management regime, however, indicates that the local practitionerslack modern scientific knowledge and still follow traditional management systems. Thestudy also reveals that traditional homegardens can be a valuable tool for in situconservation of plant species and maintaining ecosystem functioning.